BIOINFORMATIC INTERPRETATION OF TRACKING GENES OF MIRNA-LET 7B AND MIRNA-LET 7C IN DEPRESSION - Dr Shamaila Wadud; Dr Sadia Fatima; Dr Rubina Nazli; Dr Roshan Ali; Dr Muhammad Irfan (Journal of Population Therapeutics and Clinical Pharmacology, 2024)
Depression, a psychiatric disorder, has a profound impact on both physical and mental health. Despite its extensive prevalence, the complexity of its underlying causes, remains largely elusive. Growing interest has focused on microRNAs , endogenous short-stranded non-coding RNAs that inhibit, gene translation and are abundant in brain tissues. This study, conducted as portion of a clinical trial involving patients with depression, examined the plasma levels of miRNA-let-7b and miRNA-let-7c, which were observed to be down-regulated, in depression but showed improvement following treatment.The study aimed, to identify molecular genes associated with depression to uncover potential pathological mechanisms through bioinformatics. Using the miRabel database, we tracked genes and pathways affected by miRNA let-7b and let-7c in the context of depression. Differentially expressed genes and pathways were identified, with 37 tracking genes implicated in long-term depression. Through these, 11 genes had the highest potential impact: MAPK3, PLA2G4F, PLA2G4B, PLA2G4C, GNAZ, CACNA1A, GNA12, GRID2, ITPR3, ITPR1, and GUCY1A3. These 11 genes affected various pathways, including the CAMKK2 pathway, CREB1 phosphorylation via NMDA receptor-mediated RAS signaling, and the regulation of neuron apoptotic processes. These pathways, are involved in neural circuits activated by stress and environmental factors, leading to intracellular signal transduction cascades that contributes to neural plasticity, in addition to cell persistence or demise. Disparity in neuronal adaptably, can lead to depression. In summary, signal transduction cascades and neuronal adaptability are crucial during the pathophysiology of depression, and these pathways are tracked by miR-let-7b and miR-let-7c.